2003
DOI: 10.1038/sj.ejcn.1601693
|View full text |Cite
|
Sign up to set email alerts
|

Structure and organisation of 47 nutrition support teams in Germany: a prospective investigation in 2000 German hospitals in 1999

Abstract: Objective: Evaluation. Contrary to the Anglo-American region, very little is known in Germany on the structure and organisation of nutrition support teams (NST). Design: Prospective investigation of the structure and organisation of German NST, using standardised interview questionnaires. Settings: Hospitals with more than 250 beds in Germany. Subjects: German NST (n ¼ 47). Interventions: Face-to-face interview in 1999, using a standardised questionnaire. Results: From a total of 2000 German hospitals, NST hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 16 publications
0
3
0
1
Order By: Relevance
“…Nevertheless, progress in establishing NSTs across European ICU has been very slow, possibly due to the lack of available evidence that demonstrates their effectiveness. A study in Germany (Shang et al. 2003) concluded that the members of NSTs rarely held the appropriate qualifications, that the consistency in care provided by such teams was non‐existent and many of those involved had other heavy clinical commitments and did not operate in an interdisciplinary mode.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, progress in establishing NSTs across European ICU has been very slow, possibly due to the lack of available evidence that demonstrates their effectiveness. A study in Germany (Shang et al. 2003) concluded that the members of NSTs rarely held the appropriate qualifications, that the consistency in care provided by such teams was non‐existent and many of those involved had other heavy clinical commitments and did not operate in an interdisciplinary mode.…”
Section: Discussionmentioning
confidence: 99%
“…A prospective study investigated the structure and the organization of dietary nutrition in German hospitals (29), and in conclusion, better patient care was achieved with proper nutrition. Undernutrition is a serious problem in the clinical practice (28), especially in the intensive care unit (7).…”
Section: Discussionmentioning
confidence: 99%
“…Nutrition support teams (NST) are well-established in Anglo-American countries, but in Germany and German-speaking countries, however, only 3% of hospitals have organised NST. 17,18 …”
Section: Methodological Issuesmentioning
confidence: 98%